Pengaruh Pendekatan Metode Mentessori dalam Membentuk Karakter Kemandirian pada Anak Usia Dini - Kristiani Linda Yuliastutie; Supriyadi (Arden Jaya Publisher, 2022)
This article aims to determine the effect of the Montessori method in shaping the character of independence in early childhood. This Field Research Method was conducted through observation, interviews, and documentation of the Montessori curriculum at the Global Prestasi Montessori school, Bekasi City. Early childhood is a golden period that determines further development, so that the pedagogic references obtained must be in accordance with the characteristics of their age. The data generated through research shows that children at Global Prestasi Montessori School (GP Montessori) Bekasi are more independent in everyday life, because the Montessori approach includes five (5) areas that teach children various things in everyday life that involve independence. and skills. This approach also encourages children's creativity by allowing children to freely choose and explore learning activities according to their interests and potential.